Ketidakefektifan Bersihan Jalan Napas dengan Tindakan Fisioterapi Dada pada Anak yang Mengalami Bronkopneumoni Di RSU UKI Jakarta: Case Study - Gloria Albertina Tehupeiory; Erita Sitorus (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Bronchopneumonia is an infiltrate spreads to both lung hemispheres starting from the terminal bronchioles which further become blocked by exudate. This is often experienced by infants and children due to bacteria, viruses, fungi, and foreign things. The annual bronchopneumonia cases in Indonesian infants is estimated in the range of 10% -20%, with the Mortality Rate is 32 deaths per 1,000 live births before the age of 5 years old. The current case study report explains an overview of bronchopneumonia and the overcome of the nursing problem of ineffective airway clearance in three pediatric patients at RSU UKI Jakarta. In this case, the nursing process approach includes interviews, observations, implementation, and documentation of results. After that, the nursing actions were implemented for 3x24 hours, in this case is teaching deep breathing exercises, effective coughing, and chest physiotherapy for every 2 hours, fulfillment of oral warm fluids to help thin phlegm, as well as psychological comfort. In this case, the patient's parents can actually perform chest physiotherapy independently to increase coughing ability so that the sputum production decreases and respiratory function restores. Therefore, it will lead to the fulfillment of oxygen needed, thus the problem of ineffective airway clearance is overcome. Eventually, it is suggested that the family becomes a constant in the child's life as well as helping the child's healing. Therefore, the involvement of the family during the family-centered treatment process is important. In addition, as nursing care providers for patients and families, nurses need to improve their quality in paying attention to the biopsycho-socio-spiritual, cultural aspects, and have a caring character as a role model to carry out promotive, preventive, curative, and rehabilitative health care. Keywords: Pediatric Nursing Care, Bronchopneumonia, Chest Physiotherapy, Ineffective Airway Clearance